SHP2 regulates skeletal cell fate by modifying SOX9 expression and transcriptional activity - Zuo, Chunlin (Bone Res, 2018)
Chondrocytes and osteoblasts differentiate from a common mesenchymal precursor, the osteochondroprogenitor (OCP), and help build the vertebrate skeleton. The signaling pathways that control lineage commitment for OCPs are incompletely understood. We asked whether the ubiquitously expressed protein-tyrosine phosphatase SHP2 (encoded by Ptpn11) affects skeletal lineage commitment by conditionally deleting Ptpn11 in mouse limb and head mesenchyme using “Cre-loxP”-mediated gene excision. SHP2-deficient mice have increased cartilage mass and deficient ossification, suggesting that SHP2-deficient OCPs become chondrocytes and not osteoblasts. Consistent with these observations, the expression of the master chondrogenic transcription factor SOX9 and its target genes Acan, Col2a1, and Col10a1 were increased in SHP2-deficient chondrocytes, as revealed by gene expression arrays, qRT-PCR, in situ hybridization, and immunostaining. Mechanistic studies demonstrate that SHP2 regulates OCP fate determination via the phosphorylation and SUMOylation of SOX9, mediated at least in part via the PKA signaling pathway. Our data indicate that SHP2 is critical for skeletal cell lineage differentiation and could thus be a pharmacologic target for bone and cartilage regeneration.